K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

10 tháng 9 2015

x<-1=>x+1<=0

|x+1|=-x-1

x<-1=>2-x>1>0

|2-x|=2-x

N=2-x+3(x+1)=2-x+3x+3=2x+5

5 tháng 1 2021

\(A=\frac{x}{x-1}+\frac{3}{x+1}-\frac{5x}{x^2-1}\)

\(=\frac{x\left(x+1\right)}{\left(x-1\right)\left(x+1\right)}+\frac{3\left(x-1\right)}{\left(x-1\right)\left(x+1\right)}-\frac{5x}{\left(x-1\right)\left(x+1\right)}\)

\(=\frac{x^2+x}{\left(x-1\right)\left(x+1\right)}+\frac{3x-3}{\left(x-1\right)\left(x+1\right)}-\frac{5x}{\left(x-1\right)\left(x+1\right)}\)

\(=\frac{x^2+x+3x-3-5x}{\left(x-1\right)\left(x+1\right)}=\frac{x^2-x-3}{\left(x-1\right)\left(x+1\right)}\)